Buying and Selling Practices in the Malimit Customary Law as Examined by the Theory of Ba'i Muzayyadah: Case Study in Cubadak Timur Village, Duo Koto District, Pasaman Regency - Muchlis Bahar; Fauzan Hamzah; Ilham Roozman (International Journal of Science and Society, 2026)
Looking at Pasaman Regency, specifically in Nagari Cubadak Timur, a traditional buying and selling practice was found, which is commonly referred to by the community as maliit. This practice clearly contradicts the auction buying and selling in Islam, which is commonly referred to as Ba'i muzayyadah, where in malimit each bid price is taken to belong to the malimit committee. This study aims to analyze the implementation of auction buying and selling practices in the malimit tradition carried out by the community in Nagari Cubadak Timur, examine the differences between the malimit practice and the concept of ba'i muzayyadah in Islamic law, and review the malimit practice based on sharia principles in buying and selling, especially from the perspective of ba'i muzayyadah. As for answering these questions, the researcher conducted field research by going directly to the field to collect data and information from the community directly involved in this malimit practice. The data obtained were then analyzed using qualitative descriptive methods. The research results indicate that the practice of malimit is carried out through a tiered bidding system by participants, where only the final bidder acquires the auctioned item, while previous bidders contribute a percentage of the price to the malimit committee as a form of community cooperation. This research also found a difference between the practice of malimit and the concept of ba'i muzayyadah in Islamic law. In ba'i muzayyadah, the transaction is conducted purely based on a sale and purchase agreement, so only the highest bidder is obligated to pay and is entitled to the item, while other participants who lose the bid have no obligations. Meanwhile, in the practice of malimit, the auctioned items come from voluntary community donations, and the proceeds are used for the benefit of the mosque and social activities. Furthermore, the practice of malimit essentially fulfills important elements of Sharia principles, such as clarity of the goods, price, and acceptance of the contract during the auction process.